A Tourist’s Income, Satisfaction, and Loyalty: a Multivariate Analysis: ANÁLISIS MULTIVARIANTE (Dimensión Empresarial, 2022)
This study analyzes the effect of income on a group of internal-external drivers of tourist satisfaction and loyalty. A total of 810 questionnaires were applied to visitors from a prominent tourist destination in Chile (La Serena). The data was analyzed using a structural equation modeling and association tests. The results highlighted various attributes of external satisfaction (hospitality, beauty, gastronomy and security) and internal (disconnection, economy and newness). Also, it was found that the influence of attributes depends on income. It is concluded that the configuration of a tourist experience based on the key drivers of satisfaction, would increase tourist loyalty.